“All of Me Is Completely Different”: Experiences and Consequences Among Victims of Technology-Assisted Child Sexual Abuse - Joleby, Malin; Lunde, Carolina; Landström, Sara; Jonsson, Linda S. (Frontiers in Psychology, 2020)
The aim of the present study was to gain a first-person perspective on the experiences of technology-assisted child sexual abuse (TA-CSA), and a deeper understanding of the way it may affect its victims. Seven young women (aged 17-24) with experience of TA-CSA before the age of 18 participated in individual in-depth interviews. The interviews were teller-focused with the aim of capturing the interviewee’s own story about how they made sense of their experiences over time, and what impact the victimization had on them in the short and long terms. Thematic analysis of the interviews revealed a broad range of abusive experiences that had profoundly impacted the individuals’ lives, health and self-concepts. Three dominant themes emerged from the analysis – From thrilling to abusive, Negative effect on health and wellbeing, and A new self after the abuse. From thrilling to abusive captures the wide range of experiences described, starting from the child’s own sexual curiosity to descriptions of having been manipulated or threatened into engaging in sexual activity, as well as the sometimes long and complex process of understanding the severity of one’s experiences. Negative effect on health and wellbeing describes the victimization’s comprehensive impact on the life and health of the participants, how they blamed themselves for what had happened, and the struggle of having to live with the constant fear of pictures from the abuse resurfacing. A new self after the abuse depicts how the victimization impacted the way participants viewed and thought about themselves in relation to others, and distorted their views of their bodies. The findings are discussed in relation to previous research on both offline CSA and TA-CSA, as well as theoretical and practical implications.